Perfusion Imaging - Gunther, Matthias (Journal of magnetic resonance imaging, 2014)
MRI has become a reliable tool in medical imaging for assessing morphological and functional details of the human body in a noninvasive manner. Perfusion is an important parameter to assess status and functionality of tissue and organs. This review summarizes the different approaches to measure perfusion based on MRI. Some basics of the theoretical background are provided as well as measurement techniques with and without contrast media are described. J. Magn. Reson. Imaging 2014;40:269–279. © 2013 Wiley Periodicals, Inc.